Comparative efficacy and safety of no-touch versus conventional vein harvesting techniques in coronary artery bypass grafting: a systematic review and meta-analysis - Raheel Ahmed; Naveed Ahmed Khan; Muhammad Abdullah Ali; Umama Alam; Fazia Khattak; Zaryab Bacha; Fatima Sajjad; Asad Iqbal Khattak; Abdullah Afridi; Sufyan Shahid; Maheen Sheraz; Alifa Sabir (Open Heart, 2025)
Objective This meta-analysis aims to compare the clinical outcomes of the no-touch (NT) and conventional (CON) vein harvesting techniques in patients undergoing coronary artery bypass grafting (CABG).Methods We conducted a systematic review and meta-analysis following the guidelines of the Cochrane Handbook and PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) statement. We searched PubMed, Embase and Web of Science for randomised controlled trials (RCTs) comparing NT and CON vein harvesting techniques in CABG patients. Data were extracted on primary outcomes (graft failure incidence per patient, graft occlusion incidence per patient and leg infection) and secondary outcomes (revascularisation, all-cause death, myocardial infarction). Statistical analysis was performed using Review Manager V.5.4, with risk ratios (RRs) calculated for binary outcomes.Results Seven RCTs involving 4176 patients were included. The NT group showed a significantly lower risk of graft failure incidence per patient (RR=0.74, p=0.0001) and graft occlusion incidence per patient (RR=0.62, p=0.0002) compared with the CON group. However, the NT group had a higher risk of leg infection (RR=1.91, p<0.00001). No significant differences were observed between groups for revascularisation (p=0.46), all-cause death (p=0.87), or myocardial infarction (p=0.95).Conclusions The no-touch vein harvesting technique is associated with reduced graft failure incidence per patient and graft occlusion incidence per patient compared with conventional harvesting techniques in CABG, though it increases the risk of leg infection. These findings suggest NT as a preferable technique for improving graft patency but highlight the need for caution regarding leg infection.PROSPERO registration number CRD42025646500.